2016
DOI: 10.1016/j.cmet.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Pdgfrβ+ Mural Preadipocytes Contribute to Adipocyte Hyperplasia Induced by High-Fat-Diet Feeding and Prolonged Cold Exposure in Adult Mice

Abstract: Summary The expansion of white adipose tissue (WAT) in obesity involves de novo differentiation of new adipocytes; however, the cellular origin of these cells remains unclear. Here, we utilize Zfp423GFP reporter mice to characterize adipose mural (Pdgfrβ+) cells with varying levels of the preadipocyte commitment factor Zfp423. We find that adipose tissue contains distinct mural populations, with levels of Zfp423 distinguishing adipogenic from inflammatory-like mural cells. Using our “MuralChaser” lineage track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
306
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(325 citation statements)
references
References 30 publications
17
306
1
1
Order By: Relevance
“…The hypothesis of a perivascular origin of adipogenesis is also supported by mural cell expression of Zfp423 (Gupta et al 2012;Vishvanath et al 2016). Zfp423 is a multizinc finger transcription factor that regulates preadipocyte Pparγ expression and adipocyte differentiation in vitro and in vivo (Gupta et al 2010).…”
Section: Pdgfrαmentioning
confidence: 88%
“…The hypothesis of a perivascular origin of adipogenesis is also supported by mural cell expression of Zfp423 (Gupta et al 2012;Vishvanath et al 2016). Zfp423 is a multizinc finger transcription factor that regulates preadipocyte Pparγ expression and adipocyte differentiation in vitro and in vivo (Gupta et al 2010).…”
Section: Pdgfrαmentioning
confidence: 88%
“…At the cellular level, adipogenesis occurs in two major phases: first, precursors are committed to preadipocytes, and second, preadipocytes terminally differentiate into mature lipid-laden adipocytes (Rosen and MacDougald, 2006;Rosen and Spiegelman, 2014). Although the latter process has been studied in detail, the origin and identity of the adult white adipocyte progenitor niche remain a subject of debate (Vishvanath et al, 2016).…”
Section: Origins Of Adult Adipose Tissue Progenitor Cellsmentioning
confidence: 99%
“…Interestingly, PdgfRβ expression only partially overlapped with GFP expression, indicating that preadipocytes derive from a subset of specialized PdgfRβ + pericytes (Gupta et al, 2012). Recent studies suggest that differentiation from Zfp423 + precursors occurs predominantly in pgWAT, a depot where adipocyte hyperplasia substantially contributes to increased tissue mass (Jeffery et al, 2015;Vishvanath et al, 2016;Wang et al, 2013). As indicated above, these data are in line with mesenchymal stem cells giving rise to adipocytes given that similar to mesenchymal stem cells, fluorescence-activated cell scanning (FACS)-sorted pericytes are multipotent, even after long-term passaging in culture (Crisan et al, 2008).…”
Section: Pericytesmentioning
confidence: 99%
“…Alternatively, Sca1 + progenitor cells (a subpopulation of adipogenic progenitors) can be induced and differentiated into brown-like adipocytes with bone morphogenetic protein 7 (BMP7) stimulation in the skeletal muscle and subcutaneous white fat (Schulz et al 2011). On the other hand, studies have shown that beige adipocytes can be derived from interconversion from white adipocytes or through transdifferentiation of matured white adipocytes in WAT (Himms-Hagen et al 2000, Barbatelli et al 2010, Rosenwald et al 2013, given that PDGFRα + preadipocytes are not recruited and do not significantly contribute to cold-induced WAT browning (Lee et al 2015b, Vishvanath et al 2016. In addition, Lee and coworkers show that the newly observed UCP1 positive cells derived from adiponectin + unilocular white adipocytes rather than PDGFRα + preadipocytes in inguinal WAT (Lee et al 2015b).…”
Section: Characteristics Of Adipocytesmentioning
confidence: 99%